Specific Features of the Course of Toxocariasis Chorioretinitis - I. A. Gndoyan; A. V. Petrayevsky; E. Yu. Sakharova; K. S. Trishkin (Oftalʹmologiâ, 2021)
Toxacariasis is a parasitic disease from the group of nematodoses, the causative agents of which are toxocaras of dogs and cats (Toxocara canis and Toxocara mystax). Most often, the source of human invasion is dog — the main host of the parasite. Invasion occurs when helminth's eggs are ingested by means contaminated food, water, accidental geophagy, and direct contact with a dog. In the human gut, the larva releases from the egg and migrates, causing a general parasitic infestation known as “visceral migrating larvae” (Visceral larval migrans). Toxocara settles in various organs (lungs, spleen, liver, eyes, brain), which causes the local inflammatory and allergic reactions. The incidence of toxocariasis is a serious problem in recent years, especially in large cities. Each year, relatively low rates of toxocariasis and sporadic ocular infestations are recorded. This situation does not indicate stability of the situation, but rather may be due to insufficient alertness of ophthalmologists in relation to the toxacarous etiology of the inflammatory process in the eye, which leads to incomplete examination of patients and diagnostic errors. An ocular form of toxocariasis may manifest as granulomatous choroiditis, chorioretinitis and parsplanitis with the formation of peripheral granulomas and vasculitis. Complications of these inflammatory diseases are traction retinal detachment, and with a long course, chronic endophthalmitis which develops with the outcome in subatrophy and atrophy of the eye-globe, leading to its death. The disease occurs in children and adult patients. The ophthalmologists should be on the alert to the toxacariasis etiology of the inflammatory process in the choroid and retina. The article cites two case reports of toxacarous chorioretinitis (females of 53 and 57 y.o.) with development of posterior vitreous detachment and hemophthalmos. The dynamics of the pathological process, diagnostic approaches and treatment tactics are described.